The Function of Fucosylation in Progression of Lung Cancer - Jia, Liyuan; Zhang, Jing; Ma, Tianran; Guo, Yayuan; Yu, Yuan; Cui, Jihong (Frontiers in Oncology, 2018)
Lung cancer is a disease that influences human health and has become a leading cause of cancer mortality worldwide. However, it is frequently diagnosed at the advanced stage. It is necessary by means of biology to identify specific lung tumor biomarkers with high sensitivity. Glycosylation is one of the most important post-translational modifications and is related to many different diseases. It is involved in numerous essential biological processes, such as cell proliferation, differentiation and migration, cell-cell integrity and recognition, and immune modulation. However, little was known about deregulation of glycosylation in lung cancer and contribution to tumor–microenvironment interactions. Among the numerous glycosylations, fucosylation is the most common modification of glycoproteins and glycosylated oligosaccharides. Increased levels of fucosylation have been detected in various pathological conditions, as well as in lung cancer. In this article, we reviewed the role of fucosylation in lung cancer. We highlighted some of the fucosylation alterations currently being pursued in sera or tissues of lung cancer patients. Moreover, we elaborated on the regulation mechanism of fucosylation in proliferative invasion and metastasis of lung tumor cells. In summary, alterations in fucosylation provide potential biomarkers and therapeutic targets in lung cancer.